2009
DOI: 10.1103/physrevb.79.184419
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and magnetic structure ofTbNi2Mn

Abstract: The crystal and magnetic structures of the TbNi 2 Mn compound have been refined by the Rietveld analysis of neutron powder-diffraction data. The compound has a cubic C15b-type structure, in which Mn atoms partially occupy both the 4a and 16e sites. Bulk magnetization measurements revealed magnetic ordering below the Curie temperature T C = 142 K. The values of magnetic moment are different for the Tb ion at the 4a and 4c positions. In the 4c site, the Tb moment is determined to be 5.4 B / Tb ion. The low value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…Their Curie temperatures were found to be considerably higher than that of the corresponding RNi 2 compounds whereas the spontaneous magnetic moments are smaller than that of the corresponding RNi 2 alloys [5,6]. In the RNi 2 Mn alloys, it is assumed that the Ni atoms have a negligible magnetic moment whereas Mn atoms possess a large magnetic moment directed opposite to that of the R atoms.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Their Curie temperatures were found to be considerably higher than that of the corresponding RNi 2 compounds whereas the spontaneous magnetic moments are smaller than that of the corresponding RNi 2 alloys [5,6]. In the RNi 2 Mn alloys, it is assumed that the Ni atoms have a negligible magnetic moment whereas Mn atoms possess a large magnetic moment directed opposite to that of the R atoms.…”
Section: Introductionmentioning
confidence: 91%
“…In the RNi 2 Mn alloys, it is assumed that the Ni atoms have a negligible magnetic moment whereas Mn atoms possess a large magnetic moment directed opposite to that of the R atoms. [5,6]. Considering the similarities between RNi 2 and RCo 2 compounds, it is of importance to study such an influence of Mn on the latter compounds as well.…”
Section: Introductionmentioning
confidence: 99%
“…Such a moment is surprisingly small for a ferromagnetic state; this result suggests that the Mn magnetic moment may be antiparallel across the 8a and 16d sites for which approximately equal occupancy has been found through x-ray diffraction. 13 If Mn atoms at these two sites are ordered in opposite directions, then XMCD will only be able to detect the small amount of net moment even though a moment as large as 1.4 μ B has been reported by neutron diffraction 14 which is, of course, used to determine the full magnetic moment from the antiferromagnetic state. Antiparallel magnetic coupling of Mn across the two sublattices (z=1/8, 5/8 and 3/8, 7/8) at the 16d sites has been observed in TbMn 2 by neutron diffraction.…”
Section: Resultsmentioning
confidence: 99%
“…This class of materials normally crystallizes in the MgCu 2 -type Laves phase (C15 space group Fd-3m). 13 However, a different phase of structure (C15b space group F-43m) has also been reported for TbNi 2 Mn by Mushnikov et al (2009). 14…”
Section: Introductionmentioning
confidence: 96%
“…Rietveld refinements of x-ray and neutron diffraction patterns of RNi 2 Mn compounds, demonstrated that Mn atoms occupy two inequivalent crystal sites: the 8a and 16d [1,2,4,5]. As part of our systematic investigation of the magnetic properties of this novel RNi 2 Mn system, here we present a detailed investigation of the critical magnetic behavior of DyNi 2 Mn( 57 Fe) around the magnetic transition temperature by DC magnetisation (10-300 K) and 57 Fe Mössbauer spectroscopy measurements.…”
Section: Introductionmentioning
confidence: 99%